2018
DOI: 10.1055/s-0038-1653974
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of the Ophthalmology Curriculum in Medical School

Abstract: There is no national standard for ophthalmology curricula in U.S. and Canadian medical schools, and over the past 15 years, fewer schools are requiring ophthalmology rotations. AbstractPurpose There is no national standard for ophthalmology curricula in U.S. and Canadian medical schools. We aim to evaluate medical students' perceptions of the current ophthalmology curriculum without mandatory rotation at New York University School of Medicine (NYUSOM). Design A cross-sectional Internet survey. Methods A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…12 Likewise, more than half of the students at New York University School of Medicine felt uncomfortable diagnosing eye emergencies, and they were less confident in testing visual acuity and using a direct ophthalmoscope. 13 In the present investigation, no significant differences in suitability scores or rates were reported according to residency levels and the region of ophthalmology programs. The same applies to the subcategories of the assessment, including the adequacy and effectiveness of the program, as well as the required improvements.…”
Section: Discussioncontrasting
confidence: 56%
“…12 Likewise, more than half of the students at New York University School of Medicine felt uncomfortable diagnosing eye emergencies, and they were less confident in testing visual acuity and using a direct ophthalmoscope. 13 In the present investigation, no significant differences in suitability scores or rates were reported according to residency levels and the region of ophthalmology programs. The same applies to the subcategories of the assessment, including the adequacy and effectiveness of the program, as well as the required improvements.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies have reported medical students lacking in ophthalmologic knowledge 13 or lacking proficiency in basic ocular examination skills. 14 Incorporating focused training and clinical opportunities in ophthalmology can be inherently challenging for medical schools with otherwise established curricula and/or limited time and resources. More challenges might occur if an institution lacks an ophthalmology department or residency program, as I encountered in my medical school career.…”
Section: The Limits Of Medical School Curriculamentioning
confidence: 99%
“…The required ophthalmology rotation at UPSOM fills a gap in medical school training. Most medical students lack the confidence to perform eye examinations, 9 , 10 yet competency in the basics of ophthalmology is essential to safely evaluate patients with eye complaints in primary care, emergency room, neurology, and other nonophthalmologic settings. 18 , 19 Above-average clinical grades, high exam scores, and completed learning logs show that the UPSOM clerkship effectively familiarized students with ophthalmic equipment, diagnosis, and management.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Although these guidelines are in place, many medical students still report discomfort in performing clinical techniques such as direct ophthalmoscopy. 9 , 10 A lack of exposure to ophthalmology may result in students discounting ophthalmology as a career. In addition, physicians that graduate from medical school without ophthalmology experience are unlikely to understand the importance of eye health and the scope of practice of ophthalmology.…”
Section: Introductionmentioning
confidence: 99%